Complexity in unclassified auto-inflammatory disease: a case report illustrating the potential for disease arising from the allelic burden of multiple variants - Lori B. Tucker; Lovro Lamot; Iwona Niemietz; Brian K. Chung; David A. Cabral; Kristin Houghton; Ross E. Petty; Kimberly A. Morishita; Gillian I. Rice; Stuart E. Turvey; William T. Gibson; Kelly L. Brown (BMC, 2019)
Abstract Background Despite recent advances in the diagnosis and understanding of many autoinflammatory diseases, there are still a great number of patients with phenotypes that do not fit any clinically- and/or genetically-defined disorders. Case presentation We describe a fourteen-year-old boy who presented at two and a half years of age with recurrent febrile episodes. Over the course of the disease, the episodes increased in frequency and severity, with new signs and symptoms continuing to appear. Most importantly, these included skin changes, splenomegaly and transaminitis. Only partial control of the disease was achieved with anti-IL-1 therapy. Extensive investigation showed generalized inflammation without immune deficiency, with increased levels of serum amyloid A and several pro-inflammatory cytokines including interferon-γ, as well as an increased type I interferon score. Exome sequence analysis identified P369S and R408Q variants in the MEFV innate immunity regulator, pyrin (MEFV) gene and T260 M and T320 M variants in the NLR family pyrin domain containing 12 (NLRP12) gene. Conclusion Patients with unclassified and/or unexplained autoinflammatory syndromes present diagnostic and therapeutic challenges and collectively form a substantial part of every cohort of patients with autoinflammatory diseases. Therefore, it is important to acquire their full genomic profile through whole exome and/or genome sequencing and present their cases to a broader audience, to facilitate characterization of similar patients. A critical mass of well-characterized cases will lead to improved diagnosis and informed treatment.